Exact determination of asymptotic CMB temperature-redshift relation - Hahn, Steffen; Hofmann, Ralf (Arxiv, 2017)
Based on energy conservation in a Friedmann-Lemaitre-Robertson-Walker (FLRW) Universe, on the Legendre transformation between energy density and pressure, and on nonperturbative asymptotic freedom at high temperatures we derive the coefficient $ν_{\rm CMB}$ in the high-temperature ($T$) -- redshift ($z$) relation, $T/T_0=ν_{\rm CMB}(z+1)$, of the Cosmic Microwave Background (CMB). Theoretically, our calculation relies on a deconfining SU(2) rather than a U(1) photon gas. We prove that $ν_{\rm CMB}=\left(1/4\right)^{1/3}=0.629960(5)$, representing a topological invariant. Interestingly, the relative deviation of $ν_{\rm CMB}$ from the critical exponent associated with the correlation length $l$ of the 3D Ising model, $ν_{\rm Ising}=0.629971(4)$, is less than $2× 10^{-5}$. We are not yet in a position to establish a rigorous theoretical link between $ν_{\rm CMB}$ and $ν_{\rm Ising}$ as suggested by the topological nature of $ν_{\rm CMB}$ and the fact that both theories share a universality class. We do, however, line out a somewhat speculative map from the physical Ising temperature $θ$ to a fictitious SU(2) Yang-Mills temperature $T$, the latter continuing the asymptotic behavior of the scale factor $a$ on $T/T_0$ for $T/T_0\gg 1$ down to $T=0$, and an exponential map from $a$ to $l$ to reproduce critical Ising behavior.